EDUKASI TENTANG KESEHATAN REPRODUKSI BAGI MASYARAKAT KRISTEN PAPUA - Napitupulu, Abraham Geraldi (Jurnal Likhitaprajna, 2023)
This research is a result of STT Bethel Indonesia college student's dedication to Papuan people as evidence of our concern about highly HIV/AIDS cases in province of Papua. Papua is a province inhabited by a majority Christian population, but the reality of highly HIV/ AIDS cases in this province means low quality of reproductive health for the people of Papua. The implementation method which used in these activities are Webinar with explanation about the issues of reproductive health from the speaker, discussion interactive from the participants and speaker through questions and answers session, journal publishing as a result of this activities. As a result of this activities that have been carried out are the participants have received education about knowledge of reproductive organs, the functions and kinds of diseases on reproductive organs. The participants also have received education about HIV/AIDS anticipation and received practical tips to maintain reproductive health.